IRMNG 2006–2016: 10 Years of a Global Taxonomic Database - Rees, Tony; Vandepitte, Leen; Decock, Wim; Vanhoorne, Bart (Biodiversity Informatics, 2017)
IRMNG, the Interim Register of Marine and Nonmarine Genera, was commenced in 2006 as an initiative of the Australian OBIS Node (OBIS Australia) following an analysis of the taxonomic names management needs of the Ocean Biogeographic Information System (OBIS). The main objectives were to produce a hierarchical classification of all life, both extant and fossil, to at least generic level (and to species as data were readily available) and to provide a tool to distinguish marine from nonmarine, and extant from fossil taxa. Over its first 10 years of operation IRMNG has acquired almost 487,000 of an estimated 510,000 published genus names (including both valid names and synonyms) in addition to almost 1.8 million species names, of which 1.3 million are considered valid. Throughout this time IRMNG data have been available for public query via a dedicated web interface based at CSIRO in Australia, as well as being supplied as bulk downloads for use by a range of global biodiversity projects. Over the period 2014-2016 responsibility for the system has been passed to the Data Centre Division of the Flanders Marine Institute (VLIZ) in Belgium, which is continuing the maintenance and development of IRMNG at its new web location, www.irmng.org. With its present estimated holdings of >95% of all published genus names (plus associated authorities and years of publication) across all taxonomic domains, including fossil as well as extant taxa, within an internally consistent taxonomic hierarchy, IRMNG is at present uniquely placed to provide an overview of “all life” to at least generic level, to permit the discovery of trends in publication of genera through time, to provide preliminary information on the marine vs. nonmarine and extant vs. fossil status of the taxa concerned, and to generate lists of both unique and non-unique names (homonyms sensu lato) for the benefit of users of biodiversity data.